Perspektif filsafat ilmu dalam ilmu pemasaran - Lerbin R Aritonang (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2006)
Several decades ago, the scientific status of knowledge is based on logical positivism. In the next periods, logical positivism begin to be questioned by philosophers. They propose new paradigms of knowledge in philosophy of science. These new paradigms encouraged scholars to develop their knowledge. This article describes the implications of the new paradigms in science of marketing.